2021
DOI: 10.3389/fpsyt.2021.737666
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Maternal Postnatal Anxiety and Its Association With Demographic and Socioeconomic Factors: A Multicentre Study in Italy

Abstract: Anxiety is a common perinatal disorder that can cause severe adverse consequences. This study (a) assesses the prevalence of maternal postnatal anxious symptomatology, and (b) analyses its association with demographic and socioeconomic variables as well as obstetric and other psychosocial variables. The assessment included 307 mothers aged ≥18 years with a biological baby aged ≤ 52 weeks and from seven Italian healthcare centres, evaluated using a Psychosocial and Clinical Assessment Form (also covering demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(66 reference statements)
3
4
0
Order By: Relevance
“…Our study signposts that approximately one in three mothers with preterm neonates in the NICU reported experiencing anxiety. These findings align closely with the prevalence reported by Benner and Cenna with reported prevalence as 26.5% and 34.2% respectively (13, 14) . In contrast, Dannis et al and Radosn et al reported a significantly lower prevalence of anxiety, approximately 50% less than what we observed in our study (12, 15) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study signposts that approximately one in three mothers with preterm neonates in the NICU reported experiencing anxiety. These findings align closely with the prevalence reported by Benner and Cenna with reported prevalence as 26.5% and 34.2% respectively (13, 14) . In contrast, Dannis et al and Radosn et al reported a significantly lower prevalence of anxiety, approximately 50% less than what we observed in our study (12, 15) .…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we found that primiparity significantly increased the risk of postnatal maternal anxiety, supporting earlier research that linked anxiety symptoms to first-time mothers (14) . It is generally accepted that multiparous mothers have more experience, training, and expertise in parenting, all of which are protective factors against anxiety (18) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been reported that the prevalence of maternal postnatal anxious symptomatology was 34.5% at 1-24 weeks postpartum, and 30.8% at >24 weeks postpartum, which seriously affects maternal mental health and postpartum quality of life (Cena et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the prevalence of maternal postnatal anxious symptomatology was 34.5% at 1–24 weeks postpartum, and 30.8% at >24 weeks postpartum, which seriously affects maternal mental health and postpartum quality of life (Cena et al, 2021 ). Our results showed that the SAS and SDS scores of patients that received the IMB model of nursing were significantly lower than those who received routine nursing.…”
Section: Discussionmentioning
confidence: 99%